Factors influencing double brooding in Eurasian Hoopoes Upupa epops. (11th August 2014) - Hoffmann, Jael; Postma, Erik; Schaub, Michael; Smart, Jen
<x xml:space="preserve">Abstract</x> Double brooding may be a good strategy for short‐lived species to maximize annual and lifetime reproductive success (ARS and LRS, respectively). Nevertheless, there is typically individual variation in the probability of producing a second clutch. Here we evaluate factors that influence the decision to double brood in the Eurasian Hoopoe Upupa epops. Analyses of an 11‐year dataset showed that 36% of the females and 21% of the males produced a second clutch after successfully raising a first clutch. Double‐brooded females had higher ARS (9.1 ± 1.9 fledglings; mean ± se) and LRS (0.93 ± 0.08 recruits) than single‐brooded females (ARS: 4.5 ± 2.1 fledglings; LRS: 0.36 ± 0.03 recruits). This suggests that double brooding is adaptive in Hoopoes, and raises the question of why most individuals only produce one clutch per season. The probability of double brooding varied only slightly between years, suggesting that it is influenced by individual characteristics rather than by external, population‐level environmental factors. In both sexes, the probability of double brooding increased with earlier timing of the first clutch, and the timing of reproduction was the most important factor influencing reproductive success. The latter is likely to be mediated by changes in resources during the season. The probability of double brooding also increased slightly with female age, due to differences in intrinsic quality among females rather than to a gain in experience. In contrast to many other studies, the probability of double brooding increased with an increasing number of fledglings from the first clutch, suggesting that it is a strategy of individuals of high quality. Taken together, we show that the individual quality of the breeder and the timing of their first clutches are key factors influencing the decision to double brood, and thereby that they are important determinants of reproductive performance in Eurasian Hoopoes.